Enzyme inhibition, molecular docking, and density functional theory studies of new thiosemicarbazones incorporating the 4‐hydroxy‐3, 5‐dimethoxy benzaldehyde motif. Issue 4 (27th December 2022) - Demir, Yeliz; Türkeş, Cüneyt; Çavuş, Muhammet S.; Erdoğan, Musa; Muğlu, Halit; Yakan, Hasan; Beydemir, Şükrü
Abstract: New Schiff base‐bearing thiosemicarbazones (1–13 ) were obtained from 4‐hydroxy‐3, 5‐dimethoxy benzaldehyde and various isocyanates. The structures of the synthesized molecules were elucidated in detail. Density functional theory calculations were also performed to determine the spectroscopic properties of the compounds. Moreover, the enzyme inhibition activities of these compounds were investigated. They showed highly potent inhibition effects on acetylcholinesterase (AChE) and human carbonic anhydrases ( h CAs) ( K I values are in the range of 51.11 ± 6.01 to 278.10 ± 40.55 nM, 60.32 ± 9.78 to 300.00 ± 77.41 nM, and 64.21 ± 9.99 to 307.70 ± 61.35 nM for AChE, h CA I, and h CA II, respectively). In addition, molecular docking studies were performed, confirmed by binding affinities studies of the most potent derivatives. Abstract : Thirteen new Schiff base‐bearing thiosemicarbazones (1–13 ) were obtained from 4‐hydroxy‐3, 5‐dimethoxy benzaldehyde and various isocyanates. The structures of the synthesized molecules were elucidated in detail. Compounds 1–13 showed highly potent inhibition effects on acetylcholinesterase and human carbonic anhydrases.